Análise toxicológica da nanopartícula de óxido de ferro misto (NP Fe3O4) com ligantes de sulfonato de sódio (SO3)-Na+): in vitro e in vivo - Feitosa, Karina Alves (2022)
Known for their biocompatible potential and magnetic property, iron oxide nanoparticles are the target of several studies for different applications. However, the synthesis of new nanoparticles with different physicochemical characteristics leads to unknown biological interactions that may pose health risks to their manipulators. In this study, the mixed iron oxide nanoparticle (Fe3O4 NP) with sodium (SO3)-Na+) sulfonate ligands, of interest in the energy sector, was evaluated through nanotoxicological aspects. Initially, morphological, chemical, and physical characterization of the Fe3O4 NP was performed using SEM-FEG (High-Resolution Scanning Electron Microscopy), DLS (Dynamic Light Scattering), Zeta Potential, UV-Vis (Ultraviolet-Visible Absorption Spectroscopy) and ATR-FTIR (Fourier Transform Attenuated Total Reflection Infrared Spectroscopy) techniques. For the in vitro experiments, different concentrations of Fe3O4 NP (250; 100 and 50 μg/mL) were analyzed against murine fibroblasts (LA-9) in periods of 24, 48 and 72h. Thus, its cytotoxic potential was established through analysis of mitochondrial function (MTT), morphological changes and cell internalization (Prussian Blue), production of Reactive Oxygen Species (ROS), Nitric Oxide (NO) (Griess reaction), cytokines (IL-6 and TNF), determination of cell death (flow cytometry) and analysis of clonogenic potential on the 7th day after exposure. For the in vivo experiments, mice (BALB/c) were divided into 5 experimental groups (100; 50; 25 and 10 mg/Kg of Fe3O4 NP) and were intraperitoneally exposed to 4 doses over 14 days, and the toxicity of repeated doses was evaluated. Indicative signs of toxicity, hematological parameters (overall and differential leukocyte count), liver function analyses (TGO and TGP), quantification of cytokines (IFN-ˠ; TNF; IL-6 and IL-10) and histological analysis of the organs, heart, lung, liver, spleen and kidneys were evaluated. The results showed that Fe3O4 NP has a circular shape, with heterogeneous particle distribution, compacted and agglomerate formation. There was the internalization of Fe3O4 NP for all concentrations tested in vitro (250, 50 and 100 μg/mL) in a time/dependent manner. However, the increase in ROS occurred only for the 250 μg/mL concentration. Moreover, it is suggested that this same concentration triggered a senescence process in fibroblasts (LA-9), due to the low cellular metabolism and consequent reduction in colony formation within seven days. All concentrations tested during in vivo experimentation (100; 50; 25 and 10 mg/Kg) promoted damage to mouse organs, especially to the liver. There was activation of the immune system through the production of leukocytes and pro-inflammatory cytokines. Our results contribute to the knowledge about the toxicology of iron oxide nanoparticles, demonstrating the importance of analyses in longer periods after exposure. Keywords: Nanotoxicology; Inflammation; BALB/c; LA-9; Histology; Senescence.